Cumulative Impact Assessment Analysis on Tourism Activity Patterns in the Mandalika Area of ​​Central Lombok - Reza Yudi Candra; Marni Husmita; Amylia Cahyati; Muhammad Ragib; Amelia Amelia; Suharti Rosmila Sari (CV. GovPlan Indonesia, 2026)
This study aims to evaluate tourist activity patterns and their cumulative impacts in the Mandalika Tourism Special Economic Zone (KEK Mandalika), focusing on three main attractions: the Mandalika International Circuit, Kuta Mandalika Beach, and Merese Hill. The rapid development of sport tourism and coastal tourism has increased tourist mobility between destinations, potentially generating cumulative environmental, social, and infrastructural impacts. This research employs a qualitative descriptive approach using the Cumulative Impact Assessment (CIA) framework. Data were collected through field observations, semi-structured interviews with local stakeholders, documentation, and secondary data from official tourism reports. The analysis identifies tourist movement patterns, impacted components, and the accumulation of impacts arising from interconnected activities across the three locations. A CIA interaction matrix was applied to classify impact intensity into low, moderate, and high levels. The results indicate that tourist movements are dominated by multiple and complex destination patterns, intensifying pressure within a single visit period. Environmental impacts show high cumulative pressure, particularly related to waste generation, vegetation disturbance, and noise, while infrastructure experiences significant pressure due to traffic volume and parking limitations. Socio-economic impacts are generally moderate, reflecting both economic benefits and social crowding. This study concludes that the CIA approach is effective for assessing interconnected tourism impacts and supports integrated and sustainable tourism management in Mandalika.